ANALISIS KEBERLANJUTAN SUMBER DAYA IKAN KARANG FAMILI CAESIONIDAE DI KAWASAN KONSERVASI TAMAN NASIONAL KARIMUNJAWA - Ernik Yuliana; Nurhasanah Nurhasanah; Idha Farida (Jurnal Matematika Sains dan Teknologi, 2019)
Reef fish resources are the main catch in Karimunjawa National Park. The fishing activities are feared to have an impact on the sustainability of fish resources inside and outside the conservation area. The purpose of this study is to analyze of the sustainability of reef fish resources (Family Caesionidae) in marine protected area. The study was conducted in Karimunjawa National Park (TNKJ) in Jepara Regency, Central Java, April-September 2017. Data collection was carried out by survey, observation, and deep interview methods, including primary data. Coral fish of the Caesionidae family, which were the object of research, were Caesio cuning and Caesio caerulaurea. Data collection on fish length and weight was carried out six times sampling (for six months). Examples of fish taken from three collectors in Karimunjawa Village. Water quality data was taken for analysis of pH, total dissolved solids (TDS), temperature, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), and salinity. Data analysis using FISAT II program and estimation of spawning potential ratio (SPR) using length-based spawning potential ratio analysis. To analyze management aspects of reef fishes, stakeholder analysis was carried out. The research results indicated that Caesio cuning and Caesio caerulaurea had exploitation rate values ​​of 0.69 and 0.61, in the condition of over exploited. The spawning potential ratio (SPR) value are 0.14 and 0.25 (the capacity of adult fish that is ready naturally to spawn is very small). Water quality data is below the water quality standard for marine biota, indicated that the waters of the Karimunjawa National Park was sustainable. The results of stakeholder analysis indicated that there are four parties who are the subject of management. They were fisheries management authorities and Non-Governmental Organizations (NGOs) as work partners of the management authority. Ikan karang merupakan sumber daya ikan yang menjadi tangkapan utama nelayan di Taman Nasional Karimunjawa. Penangkapan ikan tersebut dikhawatirkan berdampak pada keberlanjutan sumber daya ikan di dalam dan luar kawasan konservasi. Tujuan studi ini adalah menganalisis keberlanjutan sumber daya ikan karang Famili Caesionidae di kawasan konservasi. Studi dilakukan di Taman Taman Nasional Karimunjawa (TNKJ) Kabupaten Jepara, Jawa Tengah, April-September 2017. Pengumpulan data dilakukan dengan metode survei, observasi, dan wawancara dengan mengumpulkan data primer. Ikan karang Famili Caesionidae yang menjadi objek penelitian adalah Caesio cuning dan Caesio caerulaurea. Pengambilan data panjang dan bobot ikan dilakukan empat kali sampling (selama empat bulan). Contoh ikan diambil dari tiga pengepul di Desa Karimunjawa. Data kualitas air diambil untuk analisis pH, total dissolved solids (TDS), suhu, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), dan salinitas. Analisis data menggunakan program FISAT II dan pendugaan spawning potential ratio (SPR) menggunakan analisis length-based spawning potential ratio. Untuk menganalisis aspek pengelolaan, dilakukan analisis stakeholder. Hasil penelitian menunjukkan bahwa Caesio cuning dan Caesio caerulaurea mempunyai nilai laju eksploitasi berturut-turut 0,69 dan 0,61, berada pada kondisi over exploited. Nilai spawning potential ratio (SPR) berturut-turut adalah 0,14 dan 0,25 (kapasitas ikan dewasa yang siap memijah di alam sangat sedikit). Data kualitas air berada di bawah baku mutu perairan untuk biota laut, menunjukkan perairan TNKJ dalam kondisi berlanjut. Hasil analisis stakeholder menunjukkan ada empat pihak yang menjadi subjek pengelolaan, dan semuanya adalah pemegang otoritas pengelolaan perikanan dan Lembaga Swadaya Masyarakat (LSM) sebagai partner kerja otoritas pengelola.